Pelatihan Media Pembelajaran Sesuai Gaya Belajar Menggunakan I-Spring untuk Siswa SMP Negeri 4 Kamal Bangkalan - Risnasari, Medika; Adhani, Dwi Nurhayati; Dellia, Prita; Rozan, Muhammad Afrian; Firdausiyah, Jannatul; Putri, Nina Nariyono; Dharmasaputra, Adam (Jurnal Ilmiah Pangabdhi, 2024)
Teachers at SMPN 4 Kamal in supporting the independent curriculum need the latest knowledge about the characteristics of students with local knowledge in the technological era. In terms of skills in the field of using Information and Communication Technology (ICT), teachers already have a basis in operating computers, but teachers are still less than optimal in their skills and producing ICT-based learning media works that are tailored to students' characters, animated and interactive. The aim of this training activity is to improve ICT skills and produce learning media that suits the learning styles of students at SMPN 4 Kamal using the iSpring application. In implementing this activity, training/workshop and mentoring methods are applied. The results of this training are that the dominant learning style of SMPN 4 Kamal students is visual, training teachers' skills in creating and designing their own learning media by utilizing technology and communication (ICT) through the iSpring application which suits the learning styles of students at SMPN 4 Kamal, producing products digital-based adaptive learning mediausing iSpring for each teacher according to their respective subjects. This training activity is really needed by teachers as a supporter of increasing the quality of education.